Indwelling pleural catheters for benign pleural effusions: a concise review. Issue 1 (7th January 2023) - Matta, Atul
Abstract : Purpose of review: Benign pleural effusions (BPEs) are more common than malignant effusions and their treatment involves treating the underlying disease process. However, in cases refractory to medical management, pleural interventions might be necessary. Use of indwelling pleural catheters (IPCs) has been gaining popularity for patients with refractory effusion. In this review, we will focus on reviewing the data assessing safety and efficacy of IPC in patients with BPE related to congestive heart failure (CHF), hepatic hydrothorax, end-stage renal disease (ESRD) and chylothorax. Recent findings: Several small studies including the most recent randomized control trial have looked into the efficacy and safety of IPC in BPE. Majority of data come from patients having CHF and hepatic hydrothorax as the underlying cause of the effusion. Limited data are available in patients with ESRD and chylothorax. Time to pleurodesis varies but is relatively higher in this patient population. Caution must be addressed in patients with immunocompromised status given a high risk of infection. Summary: IPCs are increasingly being used in patients with BPE refractory to medical management. They can be used both for palliation and to achieve pleurodesis in some cases. Further data in the form of randomized control trials are still needed to evaluate the efficacy and safety of its use in this patient population.